Expression pattern of glycoside hydrolase genes in Lutzomyia longipalpis reveals key enzymes involved in larval digestion - Moraes, Caroline da Silva; Diaz-Albiter, Hector M.; Faria, Maiara do Valle; Sant'Anna, Maurício R. V.; Dillon, Rod J.; Genta, Fernando A. (Frontiers in Physiology, 2014)
The sand fly Lutzomyia longipalpis is the most important vector of American Visceral Leishmaniasis. Adults are phytophagous (males and females) or blood feeders (females only), and larvae feed on solid detritus. Digestion in sand fly larvae has scarcely been studied, but some glycosidase activities putatively involved in microorganism digestion were already described. Nevertheless, the molecular nature of these enzymes, as the corresponding genes and transcripts, were not explored yet. Catabolism of microbial carbohydrates in insects generally involves β-1,3-glucanases, chitinases and digestive lysozymes. In this work, the transcripts of digestive β-1,3-glucanase and chitinases were identified in the L. longipalpis larvae throughout analysis of sequences and expression patterns of glycoside hydrolases families 16, 18 and 22. The activity of one i-type lysozyme was also registered. Interestingly, this lysozyme seems to play a role in immunity, rather than digestion. This is the first attempt to identify the molecular nature of sand fly larval digestive enzymes.